Experimental research on the ultimate strength of hard aluminium alloy 2017 subjected to short-time radioactive heating - Dafang, Wu; Yuewu, Wang; Bing, Pan; Meng, Mu; Lin, Zhu (Materials in engineering, 2012)
► Ultimate strength at transient heating is critical to security design of missiles. ► We measure the ultimate strength of alloy 2017 subjected to transient heating. ► Experimental results at transient heating are lacking in strength design handbook. ► Ultimate strength of alloy 2017 experimented is much higher than handbook value. ► The results provide a new method for optimal design of high-speed flight vehicles. Alloy 2017 (Al–Cu–Mg) is a hard aluminium alloy strengthened by heat treatment. Because of its higher strength, finer weldability and ductility, hard aluminium alloy 2017 has been widely used in the field of aeronautics and astronautics. However, the ultimate strength and other characteristic mechanical parameters of aluminium alloy 2017 in a transient heating environment are still unclear, as these key mechanical parameters are lacking in the existing strength design handbook. The experimental characterisation of these critical parameters of aluminium alloy 2017 is undoubtedly meaningful for reliably estimating life span of and improving safety in designing high-speed flight vehicles. In this paper, the high-temperature ultimate strength, loading time and other mechanical properties of hard aluminium alloy 2017 under different transient heating temperatures and loading conditions are investigated by combining a transient aerodynamic heating simulation system and a material testing machine. The experimental results reveal that the ultimate strength and loading capability of aluminium alloy 2017 subjected to transient thermal heating are much higher than those tested in a long-time stable high-temperature environment. The research of this work not only provides a substantial basis for the loading capability improvement and optimal design of aerospace materials and structures subject to transient heating but also presents a new research direction with a practical application value.